2015
DOI: 10.3382/ps/pev294
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of post-mortem findings in broilers dead-on-farm and broilers dead-on-arrival at the abattoir

Abstract: Broiler mortality during transport to abattoirs (dead-on-arrival/DOA) evokes concern due to compromised animal welfare and associated economic losses. The general aim of this study was to characterize pathological lesions associated with mortality in broilers close to slaughter. The specific aim was to investigate whether disease at the end of the growth period may be a predisposing factor for DOA by describing and comparing the pathological findings in broilers dead-on-farm (DOF) in the final days of the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 28 publications
3
29
0
5
Order By: Relevance
“…For flocks with normal DOA %, the current study sampled post-mortem findings, 103 production data and journey characteristics from a database collected in a previous 104 study (Kittelsen et al, 2015). These data were collected from February 2012 to Table 210 1. more common in the normal-mortality DOA broilers than in the high-mortality group.…”
mentioning
confidence: 99%
“…For flocks with normal DOA %, the current study sampled post-mortem findings, 103 production data and journey characteristics from a database collected in a previous 104 study (Kittelsen et al, 2015). These data were collected from February 2012 to Table 210 1. more common in the normal-mortality DOA broilers than in the high-mortality group.…”
mentioning
confidence: 99%
“…DOA refers to the percentage of the flock that died in transit between the farm and the slaughterhouse. This has been widely acknowledged as an important indicator of animal welfare in numerous studies (Kittelsen et al 2015;Nijdam et al 2006;Petracci et al 2006). It reflects the conditions experienced during transport, in combination with previous life factors affecting the stress-susceptibility of individual birds.…”
Section: Animal Welfare Indicatorsmentioning
confidence: 99%
“…The pathological studies on the causes of DOAs reported by Gregory and others4 showed 0.19 per cent DOA, of which 35 per cent died from trauma, whereas Nijdam and others5 found infectious disease was present in 64.9 per cent of DOAs, with heart and circulatory problems in 42.4 per cent and trauma responsible for 29.5 per cent 6. In the examination of the DOAs, lung congestion was found in 57.2 per cent and trauma in 24.6 per cent.…”
Section: Introductionmentioning
confidence: 96%